Former Researches of Turkish Mecmuas and Their Importance for the Studiing of Our History and the History of Turkish Folk Literature (Prilozi za orijentalnu filologiju, 2017)
Numerous mecmua-s and conk-s found in the Yugoslav collections of Oriental manuscripts are the real treasury of various material first hand collected. The researchers of the Turkish folk literature gather the basic and the most reliable data about the folk poets and their works exactly from these sources. In mecmua-s and conk-s a number of poems can be found which are inspired by some historical event, or the poems about the cities, so that they represent the important historical source as well. In regard to the significance of mecrnua-s for the studiing of our culture and the history of Turkish folk literature, we must conclude that the researches in this field do not satisfy the needs, either in quality or in quantity.